Interleukin-4 Protects Dopaminergic Neurons In vitro but Is Dispensable for MPTP-Induced Neurodegeneration In vivo - Hühner, Laura; Rilka, Jennifer; Gilsbach, Ralf; Zhou, Xiaolai; Machado, Venissa; Spittau, Björn (Frontiers in Molecular Neuroscience, 2017)
Microglia are involved in physiological as well as neuropathological processes in the central nervous system (CNS). Their functional states are often referred to as M1-like and M2-like activation, and are believed to contribute to neuroinflammation-mediated neurodegeneration or neuroprotection, respectively. PD is one the most common neurodegenerative disease and is characterised by the progressive loss of midbrain dopaminergic (mDA) neurons in the substantia nigra resulting in bradykinesia, tremor and rigidity. IL4-mediated M2-like activation of microglia, which is characterised by upregulation of alternative markers Arginase 1 (Arg1) and Chitinase 3 like 3 (Ym1) has been well studied in vitro but the role of endogenous IL4 during CNS pathologies in vivo is not well understood. Interestingly, microglia activation by IL4 has been described to promote neuroprotective and neurorestorative effects, which might be important to slow the progression of neurodegenerative dieases. In the present study, we addressed the role of endogenous and exogenous IL4 during MPP+-induced degeneration of mDA neurons in vitro and further addressed the impact of IL4-deficiency on neurodegeneration in the MPTP mouse model of PD in vivo. Our results clearly demonstrate that exogenous IL4 is important to protect mDA neurons in vitro, but endogenous IL4 seems to be dispensable for development and maintenance of the nigrostriatal system as well as MPTP-induced loss of TH+ neurons in vivo. These results underline the importance of IL4 in promoting a neuroprotective microglia activation state and strengthen the therapeutic potential of exogenous IL4 for protection of mDA neurons in PD models.